Limca book of records 2003 - Ghosh, Vijya (Gurgaon Coca-Cola India, 2001)
Limca book of the Records 2001 is the best of the best.It is filled with unusual inspiring nuggets of excellence, achievement, endeavour, aspirations. This is the one book that spells out the greatness of an incredible India and its peoples information. U
Keywords: World records